(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Background: Management of Perthes disease has many controversies. The main goal of treatment is to recover the femoral head in normal shape and to reduce pain and stiffness, to improve range of motion, prevent extrusion and collapse of head, and prevent subsequent deformity. The aim of our study is to assess the early radiological outcome of Shelf osteotomy in patients with legg calve Perthes disease Methodology This case series was conducted at the Department of Orthopedics Surgery, Khyber Teaching hospital, Peshawar, in the period from February 2022 to Jan 2023. Twenty cases were included in the study. Clinical evaluation was done by using Modified Sundt criteria. Radiological parameters were followed up at 6 month. Results: A total of 20 cases were analyzed, out of which 16 patients were males (80%) and four were females (20%). The mean age at onset of disease was 8.5 years (range: 8 years to 10 years). Pre-operatively, two (10%) patients were on the initial stage and 18 (90%) patients were on the fragmentation stage (12 (60%) cases classified as lateral pillar group B and 6(30%) cases classified as group B/C). Patients were followed up for 6 months. Clinically, 15 cases (85%) were found as good according to modified Sundt criteria, 4 cases (15%) were found as fair and one was found as poor. All the radiological parameters improved significantly. Conclusion: We recommend shelf acetabuloplasty for the management of early stages of LCPD in patients with onset of the disease over eight years. This protocol of management yields favorable clinical and radiological results.